Evaluating Permenkes No. 72/2016 Pharmaceutical Service Effectiveness in an Indonesian Referral Hospital - Nyoman Sumarna; Wayan Astawa; Nyoman Suargita (Global Academy of Business Studies, 2026)
Purpose: This study evaluates the effectiveness of Indonesia's Ministry of Health Regulation No. 72/2016 (Permenkes No. 72/2016) implementation at the Pharmacy Installation of RSUP Prof. Dr. I.G.N.G. Ngoerah, a national referral hospital in Bali, Indonesia, using Steers' organizational effectiveness framework encompassing goal achievement, adaptation, and integrity dimensions. Research Methodology: A qualitative descriptive study was conducted from January to May 2024. Data were collected through in-depth interviews with key informants including the Head of Pharmacy Installation, pharmacists, pharmacy staff, and patients or visitors, supplemented by direct observation and document analysis, and were examined using thematic analysis organized around the three effectiveness dimensions. Results: Goal achievement showed partial success through Unit Dose Dispensing system implementation, formulary maintenance, medication error minimization, and standard-compliant waiting times. Adaptation demonstrated digitalization through the Hospital Information System with e-prescribing, emergency procurement mechanisms, and enhanced pharmacist competencies. Integrity revealed adherence to standard operating procedures for High-Alert and LASA drugs alongside interprofessional collaboration, though largely formalistic in character. Conclusions: Implementation has progressed but optimization remains incomplete, with adaptation emerging as the most crucial element for sustainability. Limitations: Findings are drawn from a single tertiary referral hospital and a qualitative design that limits statistical generalization. Contributions: The study offers an organizational effectiveness lens for evaluating pharmaceutical policy implementation in resource-constrained referral hospitals.